Effect of gamma radiation on structural and optical properties of ZnO and Mg-Doped ZnO films paired with monte carlo simulation - Mivolil Duinong; Rosfayanti Rasmidi; Fuei, Pien Chee; Pak, Yan Moh; Saafie Salleh; Khairul Anuar Mohd Salleh; Sofian Ibrahim (MDPI, 2022)
In space, geostationary electronics located within the outer van Allen radiation belt are vulnerable to gamma radiation exposure. In terms of application, implementing an electronic system in a high radiation environment is impossible via conventional engineering materials such as metal alloys as they are prone to radiation damage. Exposure to such radiation causes degradation and structural defects within the semiconductor component, significantly changing their overall density. The changes in the density will then cause electronic failure, known as the single event phenomena. Thus, the radiation response of material must be thoroughly investigated before the material is applied in a harsh radiation environment, specifically for flexible space borne electronic application. In this work, potential candidates for space-borne application devices: zinc oxide (ZnO) and Mgdoped ZnO thin film with a film thickness of 300 nm, were deposited onto an indium tin oxide (ITO) substrate via radio frequency (RF) sputtering method. The fabricated films were then irradiated by Co-60 gamma ray at a dose rate of 2 kGy/hr. The total ionizing dose (TID) effect of ZnO and Mg-doped ZnO thin films were then studied. From the results obtained, degradation towards the surface morphology, optical properties, and lattice parameters caused by increasing TID, ranging from 10 kGy–300 kGy, were evaluated. The alteration can be observed on the morphological changes due to the change in the roughness root mean square (RMS) with TID, while structural changes show increased strain and decreased crystallite size. For the optical properties, band gap tends to decrease with increased dose in response to colour centre (Farbe centre) effects resulting in a decrease in transmittance spectra of the fabricated films.